ANALISIS PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK DI BURSA EFEK INDONESIA - Fadhilah Asmara (2022)
This research is a quantitative study aimed at examining the effect of liquidity ratios, solvency ratios, and profitability ratios on financial distress in companies in the transportation and logistics sector on the Indonesia Stock Exchange for the period 2017 - 2021. The liquidity variable in this study is measured by the Current Ratio (CR), solvency variables are measured by Debt to Asset Ratio (DAR), and profitability variables are measured by Return On Assets (ROA). In determining the sample, this study used a non-probability sampling technique, namely purposive sampling by providing certain criteria so that 16 companies in the transportation and logistics sector were obtained as research samples. The source of data in this study is secondary data which is then carried out by logistic regression analysis and ends with a hypothesis test, which consists of a partial test (z test) and a test of the coefficient of determination. To carry out analysis tests and hypothesis testing, this study uses the EViews 12 program. The results of this study indicate that solvency has an effect on financial distress while liquidity and profitability have no effect on financial distress.